A phenomenological study of online assessment during a pandemic crisis : Insights from Malaysia, Lithuania, and Spain - Annamalai, Nagaletchimee; Ramírez García, Antonia; Mažeikienė, Viktorija; Alqaryouti, Marwan Harb; Radzuwan, Ab Rashid; Uthayakumaran, Arulselvi (Frontiers Media S.A., 2022)
Many countries, namely, Malaysia, Lithuania, and Spain, shifted to online assessment during the COVID-19 pandemic. This qualitative case study, which involved 18 undergraduate students from the three countries, was conducted to probe insights into their online assessment experience. Data were interpreted from the perspective of the expectancy-value theory of motivation, which focuses on intrinsic attainment, utility, and cost values. The findings revealed that students were motivated to complete their assessment since they experienced flexibility besides having effective assessment guidelines. The positive experiences were related to intrinsic and attainment values; however, the students were also demotivated when stressed, indicating the high-cost value. Utility value was found to overlap with cost value in this study because students were dissatisfied with the online assessment and expressed less preference for this approach in future. This contributes to our understanding that educators must consider utility values when preparing online assessments. The pedagogical implications of this study revolve around the importance of a checklist, mock exams, alternative assessment (Plan B), and video demos for an effective assessment.